How is Excitotoxicity Being Modelled in iPSC-Derived Neurons? - Jan L. Cheng; Anthony L. Cook; Jana Talbot; Sharn Perry (Neurotoxicity Research, 2024)
Excitotoxicity linked either to environmental causes (pesticide and cyanotoxin exposure), excitatory neurotransmitter imbalance, or to intrinsic neuronal hyperexcitability, is a pathological mechanism central to neurodegeneration in amyotrophic lateral sclerosis (ALS). Investigation of excitotoxic mechanisms using in vitro and in vivo animal models has been central to understanding ALS mechanisms of disease. In particular, advances in induced pluripotent stem cell (iPSC) technologies now provide human cell-based models that are readily amenable to environmental and network-based excitotoxic manipulations. The cell-type specific differentiation of iPSC, combined with approaches to modelling excitotoxicity that include editing of disease-associated gene variants, chemogenetics, and environmental risk-associated exposures make iPSC primed to examine gene-environment interactions and disease-associated excitotoxic mechanisms. Critical to this is knowledge of which neurotransmitter receptor subunits are expressed by iPSC-derived neuronal cultures being studied, how their activity responds to antagonists and agonists of these receptors, and how to interpret data derived from multi-parameter electrophysiological recordings. This review explores how iPSC-based studies have contributed to our understanding of ALS-linked excitotoxicity and highlights novel approaches to inducing excitotoxicity in iPSC-derived neurons to further our understanding of its pathological pathways.